2011
DOI: 10.1093/hmg/ddr448
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation by PRMT1 regulates nuclear-cytoplasmic localization and toxicity of FUS/TLS harbouring ALS-linked mutations

Abstract: Mutations in FUS/TLS (fused in sarcoma/translated in liposarcoma) cause an inheritable form of amyotrophic lateral sclerosis (ALS6). In contrast to FUS(WT), which is concentrated in the nucleus, these mutants are abnormally distributed in the cytoplasm where they form inclusions and associate with stress granules. The data reported herein demonstrate the importance of protein arginine methylation in nuclear-cytoplasmic shuttling of FUS and abnormalities of ALS-causing mutants. Depletion of protein arginine met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
179
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(195 citation statements)
references
References 65 publications
15
179
1
Order By: Relevance
“…As in the case of PABPN1, the binding of FUS to transportin was reduced by arginine methylation (Fronz et al , 2011 ;Dormann et al , 2012 ). The inhibition of methylation had no detectable effect on the nuclear import of wild-type FUS (Dormann et al , 2012 ;Tradewell et al , 2012 ). Thus, like the data on S. pombe Pab2, the results suggest that the concentration of transportin in the cytoplasm is sufficiently high that arginine methylation has little effect on nuclear import unless a cargo mutation weakens the affinity for transportin.…”
Section: Functional Consequences Of Pabpn1 Methylationsupporting
confidence: 59%
See 2 more Smart Citations
“…As in the case of PABPN1, the binding of FUS to transportin was reduced by arginine methylation (Fronz et al , 2011 ;Dormann et al , 2012 ). The inhibition of methylation had no detectable effect on the nuclear import of wild-type FUS (Dormann et al , 2012 ;Tradewell et al , 2012 ). Thus, like the data on S. pombe Pab2, the results suggest that the concentration of transportin in the cytoplasm is sufficiently high that arginine methylation has little effect on nuclear import unless a cargo mutation weakens the affinity for transportin.…”
Section: Functional Consequences Of Pabpn1 Methylationsupporting
confidence: 59%
“…FUS is known to carry asymmetrically dimethylated arginine residues; in contrast to PABPN1, these are not in the canonical motifs of the transportin-binding site but in an adjacent RGG domain (Rappsilber et al , 2003 ). The inhibition of arginine methylation by the use of the general inhibitor adenosine dialdehyde, knockdown of PRMT1, or deletion of the PRMT1 gene rescued the nuclear import of FUS when it was compromised by mutations in its PY-NLS (Dormann et al , 2012 ;Tradewell et al , 2012 ). As in the case of PABPN1, the binding of FUS to transportin was reduced by arginine methylation (Fronz et al , 2011 ;Dormann et al , 2012 ).…”
Section: Functional Consequences Of Pabpn1 Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, it has been established that this arginine methylation can affect their nuclear localization (Araya et al, 2005;Jobert et al, 2009;Tradewell et al, 2012). In this issue, Dormann et al (2012) sought to delve further into the mechanism by which this occurs.…”
Section: Als-fusmentioning
confidence: 99%
“…It has been previously reported that FUS undergoes arginine methylation in arginine-glycine-glycine (RGG) domains near to the NLS that impairs TNPO1 binding to RGG domains, inhibiting nuclear import (Rappsilber et al, 2003;Hung et al, 2009;Dormann et al, 2012;Tradewell et al, 2012;Yamaguchi and Kitajo, 2012;Scaramuzzino et al, 2013). Finally, phosphorylation of the C-terminal Y656 residue within the NLS of the EWSR1 protein has been shown to inhibit nuclear import (Leemann-Zakaryan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%